MAGNIT MAYDON VA ELEKTROMAGNIT INDUKSIYA HODISASINING O‘RGANILISHI - Begmuradov Shohzod Dilmurod o'g'li (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Annotation:This article discusses the nature of the magnetic field, its interaction with electric current, and the phenomenon of electromagnetic induction. It provides an overview of the fundamental laws of magnetism, such as Ampère’s law, Biot–Savart law, and Faraday’s law of electromagnetic induction. The practical applications of magnetic fields in electrical engineering, power generation, and modern technologies are also analyzed. The study emphasizes the importance of experiments and visual demonstrations in understanding the principles of magnetism and electromagnetic induction.